Analisis Strategi Bersaing pada Produk Fashion : Studi Kasus CV Racun Cinta - Lutfi Zulkarnain; Nur Uswatin Hasanah (Neolectura, 2021)
This study aims to design an alternative strategy that should be used by CV Racun Cinta in winning the fashion business competition, especially clothing distribution, by first assessing the internal and external factors that affect the business of CV Racun Cinta. This research is a qualitative descriptive study using SWOT analysis (strength, weakness, opportunity, threats). The results of this IE (Internal-External) study indicate that the position of CV Racun Cinta is in cell 1, which is growing and building with an alternative, intensive strategy and integrative strategy. Furthermore, using Porter's Five Forces Analysis.